2002
DOI: 10.1002/jclp.10099
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of efficacy for EMDR resource development and installation in the stabilization phase of treatment of complex posttraumatic stress disorder

Abstract: This article reviews the complexity of adaptation and symptomatology in adult survivors of childhood neglect and abuse who meet criteria for the proposed diagnosis of Complex Posttraumatic Stress Disorder (Complex PTSD), also known as Disorders of Extreme Stress, Not Otherwise Specified (DESNOS). A specific EMDR protocol, Resource Development and Installation (RDI), is proposed as an effective intervention in the initial stabilization phase of treatment with Complex PTSD/DESNOS. Descriptive psychometric and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0
32

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(144 citation statements)
references
References 47 publications
0
112
0
32
Order By: Relevance
“…The method works by essentially using bilateral stimulation, and/or stimuli (visual, auditory or tactile) that occur in a rhythmic left-right patern. Anchoring resources may include tactile stimulation, auditory tapping, or installing stabilizing imaginal resources through guided imagery [59].…”
Section: Eye Movement Desensitization and Reprocessing (Emdr)mentioning
confidence: 99%
“…The method works by essentially using bilateral stimulation, and/or stimuli (visual, auditory or tactile) that occur in a rhythmic left-right patern. Anchoring resources may include tactile stimulation, auditory tapping, or installing stabilizing imaginal resources through guided imagery [59].…”
Section: Eye Movement Desensitization and Reprocessing (Emdr)mentioning
confidence: 99%
“…Numerous studies reporting the use of EMDR for PTSD and phantom limb pain have noted improvements in comorbid depression scores during treatment (Korn & Leeds, 2002;Maxfield & Hyer, 2002;Schneider, Hofmann, Rost, & Shapiro, 2008;van der Kolk et al, 2007) these studies are summarized in Table 1. When treating PTSD with EMDR, comorbid depression improves in almost all cases and EMDR appears to be better at treating this than imaginal exposure (Arabia, Manca, & Solomon, 2011), waiting list controls (Hogberg et al, 2007;B.…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%
“…Only one RCT found that comorbid depression did not improve when PTSD was treated with EMDR, relaxation or biofeedback (Silver, Brooks, & Obenchain, 1995). All of the case studies and case series found an improvement in depressive symptoms when PTSD was successfully treated with EMDR (Chemtob, Nakashima, & Carlson, 2002;Korn & Leeds, 2002;Lobenstine & Courtney, 2013;Montefiore, Mallet, Levy, Allilaire, & Pelissolo, 2007;Raboni, Tufik, & Suchecki, 2006;Schneider et al, 2008;Steven M. Silver, Rogers, & Russell, 2008;Tarquinio, Schmitt, & Tarquinio, 2011;Tarquinio, Schmitt, Tarquinio, Rydberg, & Spitz, 2011). Although each case study on its own is not generalizable due to the nature of the experimental design, the growing number of such reports adds weight to the premise that, in people with PTSD, comorbid depression can be alleviated by treatment with EMDR.…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%
“…Heftige ervaringen die door delen worden bewaard, worden niet in detail verteld maar slechts aangestipt op de lijn. In dit geval geeft Patrick aan dat het beter is een bepaald stuk van de levenslijn te maken, waarbij het boze deel Rogue nog (Korn & Leeds, 2002). Na dit eerste ronde-tafelgesprek is duidelijk zichtbaar dat Rieks' zelfvertrouwen toeneemt.…”
Section: Verwerkingsfaseunclassified